PERSUASIVE STRATEGIES USED IN JOKOWI’S SPEECH IN HIS GOVERNOR ELECTION CAMPAIGN - Winda Pramithasari; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2014)
This present study is conducted to find out the types of persuasive strategies which were used in Jokowi’s speech. This study is aimed to seek the types of persuasive strategies and also the speech function related to the persuasive strategies used by Jokowi. This study is supported by Beebe & Beebe’s theory of persuasive strategy (2012) and Holmes theory of speech function (1996). The writer analyzed the speech in a standup comedy used in Jokowi campaign in 5th October 2012. The writer found eight characteristics of persuasive strategies that Jokowi used: using evidence to tell a story , considering using appeals to several emotion (hope, courage, pride,) using specific evidence, using appropriate fear appear, using new evidence, and using concrete example that help your listener visualize what you describe. The writer also found the speech function that related in persuasive strategies in Jokowi’s speech as being referential, directive, metalinguistic, expressive, and phatic.